Olivia... And the Missing Toy - Falconer, Ian, 1959- (New York : Atheneum Books for Young Readers, 2003)
When her best toy mysteriously disappears, Olivia the feisty pig is determined to find out who is responsible.
Keywords: Lost articles -- Juvenile fiction; Toys -- Juvenile fiction; Swine -- Juvenile fiction; Lost and found possessions -- Fiction; Toys -- Fiction; Pigs -- Fiction